Keefektifan Tata Ruang Kantor pada Bagian Arsip di PT Bosowa Berlian Motor Makassar - Baharuddin, Aris; Nasaruddin, Nasaruddin; Haerul, Haerul; Rahmawati, Rahmawati (Jurnal Office, 2018)
This study aims to determine the effectiveness of office layout in the archive section at PT. Bosowa Berlian Motor Makassar. This research uses quantitative descriptive research with observation, questionnaire, interview and documentation data collection techniques. The population in this study all employees at PT. Bosowa Berlian Motor, amounting to 136 people and the sample in this study as much as 50 percent, the total was 68 respondents. The data analysis technique used is by using descriptive analysis that is to present each question item using a percentage formula. The results showed that the three indicators in this study generally showed quite effective results, starting from the indicators of office spatial planning, the results of which were quite effective, indicators of employee placement whose results were quite effective, and indicators of the office's physical environment whose results were effective. Of the three indicators provide an overview that can be concluded that the office layout in the archive section at PT. Bosowa Berlian Motor Makassar as a whole is considered quite effective.